Use of Infrared Thermography for Identifying Physiological and Hematological Conditions of Young Sapera Dairy Goats - Fitra Aji Pamungkas; Bagus Priyo Purwanto; Wasmen Manalu; Ahmad Yani; Riasari Gail Sianturi (Jurnal Ilmu Ternak dan Veteriner, 2020)
Infrared thermography (IRT) is an alternative solution that can be applied to replace invasive methods currently used in the monitoring of goats' physiological and hematological parameters. This study was done to compare and correlate the physiological and hematological conditions of young Sapera dairy goats and their correlations with results obtained by IRT. Four young Sapera dairy goats (weight of 26-28 kg) were kept in the individual rearing cage. Skin surface temperature (TS), rectal temperature (TR), body temperature (TB), heartbeat (HR), respiration rate (RR), and IRT at eyes, mouth, nose, legs, left body, right body, vagina, and vulva were monitored from 6 a.m. to 6 p.m. in 2 h intervals. Blood samplings were done at the beginning and the end of the obsevation time. Results showed that IRTs at several body parts were positively correlated with physiological parameters, except for heartbeat. Negatively correlation was observed in hematological parameters. The highest correlation (r = +0.85) was observed in the correlation between the results of the left rear leg IRT on TB. It was concluded that IRT can be applied to examine goats’ physiological conditions especially body temperature.